2014
DOI: 10.1089/end.2014.0134
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Urologic Minilaparoscopy: Indications, Techniques, and Surgical Outcomes in a Multi-Institutional European Cohort

Abstract: Objectives: To provide an analytical overview of contemporary indications, techniques, and outcomes of urologic minilaparoscopy (ML) in multiple European centers. Most of the procedures were done in the upper urinary tract (133 cases, 69.2%) and were mostly with a reconstructive intent (109 cases, 56.7%). Overall operative time was 132.7 -52.3 minutes with an estimated blood loss of 60.9 -47.6 mL while the mean hospital stay was 5 -2.1 days. Most of the postoperative complications were low Clavien grade (1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 25 publications
(31 reference statements)
0
7
0
1
Order By: Relevance
“…Exclusive use of minilaparoscopy material can also give a scarless surgery and could be an excellent alternative for cases that do not require specimen retrieval [17,28]. It duplicates the principles of standard laparoscopy but offers less surgical scar and potentially less surgical trauma [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusive use of minilaparoscopy material can also give a scarless surgery and could be an excellent alternative for cases that do not require specimen retrieval [17,28]. It duplicates the principles of standard laparoscopy but offers less surgical scar and potentially less surgical trauma [28].…”
Section: Discussionmentioning
confidence: 99%
“…It duplicates the principles of standard laparoscopy but offers less surgical scar and potentially less surgical trauma [28]. The hybrid LESS that we propose is advantageous both for small size specimen extraction and for using large caliber haemostatic devices such as Ligasure™ or harmonic scalpel; however, it needs specific training and expertize [27].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of urological procedures have been successfully performed using ML, including pyeloplasty, radical nephrectomy, radical prostatectomy and adrenalectomy [7].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of surgical scarring, the use of trocars of smaller diameter, not requiring formal skin closure, could potentially translate into less pain. A broad range of common urological procedures have safely and effectively performed with this newly re-discovered technique, mostly for kidney diseases [7]. Porpiglia et al recently showed a better patients scar satisfaction using ML instruments to carry out laparoscopic pyeloplasty [8].…”
mentioning
confidence: 99%
“…Alternative techniques for minimizing access trauma without losing the advantage of triangulation, such as minilaparoscopy or small access retroperitoneoscopic technique, use miniaturized instruments [72][73][74][75] . The com bination of both access modalities (hybridLESS) has also been used 76 .…”
Section: Less and Minilaparoscopymentioning
confidence: 99%